Test protocol optimization of the heart rate-based lactate minimum test - Perret, C.; Kurzen, J. (International Journal of Sports Medicine, 2022)
The determination of the maximal lactate steady state (MLSS) requires at least two constant load tests. Therefore, different testing procedures to indirectly determine MLSS based on one single test have been developed. One such method is the application of the lactate minimum tests (LMT), where workload and heart rate-based protocols exist. The latter showed significant correlations between parameters at lactate minimum (LM) and MLSS for running and cycling. However, LM clearly underestimated MLSS. Therefore, the aim of this study was to optimize the already existing test protocol in terms of an improved agreement between LM and MLSS. Fourteen healthy endurance-trained male athletes (age: 39.7±8.2 y; height: 180.9±6.2 cm; body mass: 78.6±7.1 kg) performed four different heart rate-based LMT protocols, the original and three new protocols. Additionally, they performed several constant heart rate endurance tests for assessing MLSS exercise intensity. Heart rate, blood lactate concentration, oxygen uptake and power at LM of two of our new test protocols with an increased start intensity were closer to and no longer different from MLSS data. We conclude that these two new test protocols can be used in practice to estimate heart rate-based MLSS by means of one single exercise test.